Associação entre cepas de Escherichia coli Enteropatogência (EPEC) e crianças desnutridas residentes em Fortaleza-Ceará, Brasil: um estudo caso-controle - Santos, Ana Karolina Silva dos (2022)
Introduction: Enteropathogenic Escherichia coli (EPEC) is one of the main causes of diarrhea in children in developing countries and has a high rate of genetic variability. Objective: to characterize the distribution of genes related to EPEC virulence and copathogens in association with physical deficit, enteropathy, diarrhea and micronutrient deficiency in children living in the city of Fortaleza-CE. Material and Methods: a case-control study of malnutrition was carried out in 402 children aged 6-24 months in the city of Fortaleza, CE/Brazil. This study was part of a multicenter study entitled “Etiology, Risk Factors and Interactions of Enteric Infections and Malnutrition and the Consequences for Child Health”, or the MAL-ED study. Cases were defined as malnourished children using the underweight-for-age Z-score index (WAZ <-2) and controls were defined as nourished children using the underweight-for-age Z-score (WAZ ≥ -1) index. Samples from these children were collected and anthropometric and epidemiological data were identified for each child. Bacterial DNA extraction from fecal samples of 402 children was performed, from August 2010 to May 2013. EPEC detection was performed using multiplex PCR, using the eaeA and bfpA genes. A comprehensive molecular evaluation of enteropathogens was performed, and EPEC-positive children were investigated for 18 virulence genes (VGRs) using five panels of multiplex PCRs. Results: EPEC was detected in 30.3% of the study population, with similar proportions between cases and controls. aEPEC infections had a higher prevalence 67.2% (82/122). Children infected with EPEC showed significantly lower WHZ values than children without EPEC infection (p=0.0495). The espD virulence gene, a T3SS protein translocator, was associated (p=0.0001) with malnutrition in EPEC-positive children. The genes espD, nleBe ler (p= 0.0001; p=0.0004; p=0.0018), were associated with aEPEC-positive children. Campylobacter spp. It was associated with the case group in children with EPEC by a univariate analysis (p=0.0290; OR=0.22; 95%CI=0.05-0.082). The presence of biomarkers MPO (p=0.0078) and CD14s (p=0.0001) were associated with the control group. Conclusion: aEPEC had a high prevalence; EPEC showed a decrease in HAZ compared to children without infection; Coinfection of Campylobacter ssp. was associated with malnutrition.